Standar Resep Sebagai Dasar Perhitungan Harga Jual Kewirausahaan Kuliner - Dodik Prakoso Eko Hery Suwandojo; Rosalina Nur Annisa; Dyah Wahyuning Tyas; Meiana Maulida Hikmawati (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
Introduction: The culinary industry plays an important role in Indonesia's creative economy. This article discusses the use of standardized recipes as a basis for calculating the selling price of culinary products. The purpose of this article is to guide culinary entrepreneurs in accurately calculating production costs and determining competitive selling prices. Literature Review: The theory of this article draws on the price plus cost theory. This article highlights the importance of a standardized recipe-based selling price-setting strategy as a guideline for production costs and determination of the desired profit margin. Methods: This research uses the explanatory narrative method, with a qualitative approach. Narrative explanatory research is research that explains how something happens. Results and Discussion: This article provides the ability for culinary entrepreneurs to calculate the cost of goods and the selling price of their culinary products more consistently. Conclusion: The use of standard recipes as the basis for calculating selling prices can help culinary entrepreneurs maintain the profitability of their businesses.